Effects of irrigation activation techniques on root canal walls after post-space preparation: A scanning electron microscopy study - Dide Tekinarslan; Damla Erkal; Simay Koç; Hakan E; Kürşat Er (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2024)
Objectives: To evaluate the effect of different irrigation activation techniques (IATs) on smear layer removal after post-space preparation. Methods: Forty single-rooted mandibular premolars with no root canal treatment were selected. Teeth were decoronated at 15 mm, and apical patency was confirmed using a #10 K-file. The ProTaper Next NiTi file system was used to shape the root canal. Afterward, the root canals were filled with gutta-percha and a root canal sealer. A week later, 10-mm postspace preparation was done. Teeth were randomly divided into 4 groups based on the IATs used to activate 3 mL of 17% EDTA for 1 min: 1) control group with a conventional needle; 2) sonic irrigation (SI); 3) passive ultrasonic irrigation (PUI); and 4) laser-activated irrigation (LAI). Teeth were split longitudinally, and specimens were observed under a scanning electron microscope. Images were taken at the teeth' coronal, middle, and apical thirds at ×2000 magnification and were scored based on the presence of the smear layer. Data were analyzed statistically. Results: No statistically significant difference was observed between the IATs regarding smear layer removal (p>0.05). However, PUI was more successful at the coronal and apical third, and SI was more successful in the middle third. Conclusions: All the used IATs were effective in removing the smear layer. However, none of them removed it completely.